Features of staffs’ psychological wellbeing in higher education system of Kazakhstan (The Journal of Psychology and Sociology, 2016)
The article investigates the relationship of psychological wellbeing and success in the professional activity of the person. The understanding of term success in this work turns to the concept of stress resistance and a willingness and readiness for change of the people who are professionals in the field of education. To be more precise, those who are the teaching staff of the national universities. The introduction part suggests brief historical data about the development of the term of `psychological wellbeing. The relevance of the article is determined by the need to establish an understanding of the term psychological wellbeing in Kazakhstan, particularly in its educational system. As well as the reorientation of the work of the psychological trend in practically meaningful and relevant channel. In this article, it was suggested to analyse the psychological wellbeing as a set of objective factors derived in the appropriate scales. In addition, measurements of stress level were carried out as the main indicator of success in the professional activity of the subjects, to determine the most obvious among the parameters of psychological wellbeing of the physiological, emotional, behavioural and cognitive characteristics. The study was conducted as part of the Faculty of Humanities of one of the national universities of Kazakhstan, taking into account all its member department. Identify the general level of prosperity and the degree of stress on a sample of employees of this department. The importance of this work is due to the practice-oriented approach to the study of the structure of organizations and identify the causes of low productivity of staff borrowed from foreign practices. The basis of such practices include a thorough study of the individual and private organizations (in this case, the Faculty of Humanities of National University).During the research psychological wellbeing scales by K.Riff” and the questionnaire on stress resistance by L.Loginova were used. The results from the methods revealed interesting figures. Both from the analysing the results from each of the methods separately and while watching the correlation between them. The article includes detailed conclusions for each of the departments and the provision of specific data.
Keywords: psychological wellbeing; stress; stress resistance; change on the working place.